A RELATIONSHIP BETWEEN THE SERVICE LIFE OF THE PERMANENT WAY AND THE INHOMOGENEITY OF THE SUBSTRUCTURE - Gerber, Ulf (Science and Transport Progress, 2003)
The inhomogeneity of the substructure will be described by the so-called variance of the substructure in this paper. The result will be a formulation of the permanent way’s service life as a function of the variance of the substructure. An example will be included to illustrate the results of the calculations.